Daratumumab for autoimmune diseases: a systematic review - Martin Krusche; Ina Kötter; Lennard Ostendorf; Nikolas Ruffer; Marie-Therese Holzer; Tobias B. Huber (RMD Open)
Objective Refractory autoimmune diseases remain a significant challenge in clinical practice and new therapeutic options are needed. This systematic review evaluates the existing reported data on the CD38-targeting antibody daratumumab as a new therapeutic approach in autoantibody-mediated autoimmune diseases.Methods A protocolised systematic literature review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was performed. Two databases (Medline and Embase) were searched for suitable studies. Usage of daratumumab in non-oncological or non-transplantation associated diseases with autoimmune pathophysiology was analysed including patient characteristics, therapeutic regimen, adverse events and patient outcome.Results 38 publications reporting the clinical course of 83 patients met the inclusion criteria. Daratumumab usage was reported in therapy-refractory cases (median of 5 different previous therapies) in 24 different autoimmune diseases. The median number of applications of daratumumab was 4, mainly via intravenous applications (87%). Concomitant treatment included glucocorticoids in 64% of patients, intravenous immunoglobulins (33%) and rituximab (17%). Remission or improvement of disease was reported in 81% of patients. Autoantibody depletion or reduction was stated in 52% of patients. Death occurred in three patients (3%). Adverse events were reported in 45% of patients including application-associated reaction (20%), infection (19%) and hypogammaglobulinaemia (33%).Conclusion Targeting CD38 via daratumumab is a new promising therapeutic option in therapy refractory autoimmune diseases. Efficacy as well as optimal therapeutic regimen and management or prevention of adverse events require further investigation. Therefore, systematic clinical trials of this therapeutic approach are needed.